2022
DOI: 10.55661/jnate.974146
|View full text |Cite
|
Sign up to set email alerts
|

Comparing English language teacher education programs in Turkey and Finland

Abstract: The quality and qualifications of teachers reflect the quality of education and the success of students accordingly, and particular attention needs to be given to preservice teacher training as it is the primary step towards professionalization. Keeping this point in mind, English language teacher education programs (ELTEPs) seem to be a worthwhile research area. There is an increasing number of studies addressing ELTEPs in Turkey. Yet, comparative data on Turkey's ELTEPs and those of other countries remain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
0
0
1
Order By: Relevance
“…Inadequacy of teachers in developing and adapting materials was also a finding of Akdağ Çimen (2017) and she suggested including materials development training in teacher education programs. Parallel to the finding of the current study, Ekoç (2022) reported that the number of education faculties had risen with the increase in the number of state and private universities, which created an issue of quality. The increase is also the reason of nonstandardization among the departments of English language teaching.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 79%
See 1 more Smart Citation
“…Inadequacy of teachers in developing and adapting materials was also a finding of Akdağ Çimen (2017) and she suggested including materials development training in teacher education programs. Parallel to the finding of the current study, Ekoç (2022) reported that the number of education faculties had risen with the increase in the number of state and private universities, which created an issue of quality. The increase is also the reason of nonstandardization among the departments of English language teaching.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 79%
“…Öğretmenlerin materyal geliştirme ve uyarlama konusundaki yetersizlikleri de Akdağ Çimen'in (2017) bir bulgusu olup, öğretmen yetiştirme programlarında materyal geliştirme eğitimine yer verilmesini önermiştir. Ekoç (2022), mevcut araştırma bulgusuna paralel olarak, devlet ve vakıf üniversitelerinin sayısının artmasıyla birlikte eğitim fakültelerinin sayısının arttığını ve bunun bir kalite sorunu yarattığını bildirmiştir. Erdoğan ve Savaş'ın (2022) çalışmasında katılımcılar, YKS'nin konuşma, dinleme veya yazma becerilerinden çok, çoktan seçmeli bir sınav testi stratejisi olduğunu ve bu nedenle gerçek dil yeterliliğini kanıtlamakla sınırlı olduğunu ifade etmişlerdir.…”
Section: Tartışma Ve Sonuçunclassified